Captain america cold war ebook - Lanzing, Jackson (Captain America: Cold War (2023), 2023)
Collects Captain America: Cold War Alpha (2023) #1, Captain America: Symbol of Truth (2022) #12-13, Captain America: Sentinel of Liberty (2022) #12-13, Captain America: Cold War Omega (2023) #1. Bucky Barnes makes his deadliest move yet! The newest player in a nefarious game spanning all of civilization has teamed up with Sam Wilson's nemesis, the White Wolf! When Steve Rogers' adopted son - Ian, A.K.A. Nomad - is abducted by someone Steve thought was a friend, he suspects Bucky's hand at work and calls on Sam, Sharon Carter and Misty Knight to help get to the bottom of the attack. Why has Nomad been taken, and what does it have to do with a portal to Dimension Z opening over a secret battleground in Alaska? Has Bucky finally gone too far? And when Black Widow joins the fray, whose side is she on?